Analysis and Discussion on Operation Scene of High-speed EMS Maglev Railway - Guang CHEN (机车电传动)
Operation scene is the foundation and guidance of a project that mainly reflects the concept, demand of operation, and reflecting the function of each equipment and basis of post setting, and the linkage of the system. In order to design and construct the high-speed EMS maglev railway project in a more reasonable, efficient and comprehensive way, it is necessary to conduct systematic analysis and research on the operation scenarios. By comparing the differences between the architecture, the vehicle control modes and the line conditions of the high-speed maglev system and that of the wheel rail transit system, and on the basis of fully absorbing and borrowing the existing operation modes and scenarios of the wheel rail transit and Shanghai high-speed EMS maglev demonstration line, combined with the operation requirements of the long and large trunk lines, the framework of the operation scenarios of the high-speed EMS maglev railway was put forward, which has a certain guiding role for the follow-up research of the high-speed EMS maglev line.